INTEGRATING LOCAL CULTURE INTO ENGLISH TEACHING AND LEARNING PROCESS - Margana Margana (Universitas Muhammadiyah Surakarta, 2009)
English teachers very often question whether they have to only rely on the cultureof the target language. Such confusion appears from their mind when they are involved in setting up the process of ELTL. Many English teachers assume that theculture of the target language should be the centre of ELTL as learning languagecannot be separated from culture. As a result, English teachers overwhelmingly provide students with texts or dialogs derived from the English speaking countries which reflect native speakers’ lives and behaviours. This somehow makes students difficult to understand the English materials as students have limited prior knowledge in lieu with the culture of the target language. Very often, the selected materials contradict to students’ beliefs leading to students’ unwillingness to study English. With regard to the above problem, this paper deals with promoting local culture in the process of English teaching and learning. It aims at encouraging English teachers to integrate the local culture into ELTL. Embedding students’ local culture in ELTL is believed to facilitate students to gain the success for learning English. Added to this, having deep understanding of the local culture establishes the awareness of students’ own local culture to be promoted in global communication.Keywords: local culture, english language learning, global communication